Self-Efficacy, Self-Care Activities Management and Treatment Outcome among Type 2 Diabetes Saudi Patients: Across-Sectional Study - Abubaker Ibrahim Elbur; Abdullah Salem AlMalki; Sultan Abdullah Alharthi (Journal of Pharmacy and Nutrition Sciences, 2017)
The main aims of this study were to measure the level of diabetes management self-efficacy and adherence to self-care activities management and to identify the influence of self- efficacy on management of self-care activities and the outcome of treatment among type 2 diabetic patients. A cross-sectional study was conducted at the Diabetes Clinic; King Faisal Medical Complex during the period of June –August 2016. Patients aged >20 years and diagnosed with type 2 diabetes for at least one year. Data was collected through face-to-face interview method using a pretested and validated questionnaire. Data was processed by the software SPPS (21.0 SPSS Inc., Chicago IL, USA). P value <0.05 was considered statistically significant. A total of 300 patients were eligible. Slightly more than 50 % of them were females. Overall, 164 (54.7%) patients were classified as having high diabetes management self-efficacy. Living in the town (P = 0.006) and being married (P= 0.003) were found to be the significant predictors of high self-efficacy. There were significant associations between self-efficacy by domain and adherence to the specific self-care activity corresponding to that domain. Overall, 84 (28%) of the patients attained the target therapeutic goal for diabetes and the control was significantly more among females (33.6%) than males (22.3%), (P= 0.031). The results of the study identified many gaps related to management self-efficacy of diabetes and adherence to self-care activities. Interventions targeting the patients and their families to improve this situation are urgently needed.